2017
DOI: 10.3390/geosciences7020036
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Landslide Pre-Failure Monitoring and Forecasting Using Satellite SAR Interferometry

Abstract: Abstract:In this work, the ability of advanced satellite interferometry to monitor pre-failure landslide behaviours and the potential application of this technique to Failure Forecasting Methods (FFMs) are analysed. Several limits affect the ability of the technique to monitor a landslide process, especially during the pre-failure phase (tertiary creep). In this study, two of the major limitations affecting the technique have been explored: (1) the low data sampling frequency and (2) the phase ambiguity constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…As far as Sentinel-1 data are concerned, Intrieri et al [26] have used DInSAR time series after the occurrence of the Maoxian landslide event (Sichuan province, China), suggesting that acquisitions with a short revisiting time could be used not only as a tool for mapping unstable areas, but also for systematic landslide monitoring. In addition, Moretto et al [43] have explored the possibility to use DInSAR time series to monitor landslide in pre-failure stages by simulating accelerated slope deformation over more than 50 landslide events as they would be acquired from past, actual, and future constellations of SAR satellites, including the Sentinel-1. They concluded that, based on Sentinel-1 acquisition parameters, phase ambiguity and revisit time limitations would have allowed to follow the evolution towards failure only for a minor portion of the analyzed dataset.…”
Section: Discussionmentioning
confidence: 99%
“…As far as Sentinel-1 data are concerned, Intrieri et al [26] have used DInSAR time series after the occurrence of the Maoxian landslide event (Sichuan province, China), suggesting that acquisitions with a short revisiting time could be used not only as a tool for mapping unstable areas, but also for systematic landslide monitoring. In addition, Moretto et al [43] have explored the possibility to use DInSAR time series to monitor landslide in pre-failure stages by simulating accelerated slope deformation over more than 50 landslide events as they would be acquired from past, actual, and future constellations of SAR satellites, including the Sentinel-1. They concluded that, based on Sentinel-1 acquisition parameters, phase ambiguity and revisit time limitations would have allowed to follow the evolution towards failure only for a minor portion of the analyzed dataset.…”
Section: Discussionmentioning
confidence: 99%
“…With a specific look at landslide phenomena, on the other hand, Moretto et al [6] explore the potential of satellite InSAR methods to sense pre-failure landslide movements and to feed into failure forecasting methods. For 56 landslide sites with monitoring data available in the scientific literature, the authors collate pre-failure deformation information from on site and remote monitoring instruments, such as inclinometers, ground-based InSAR, and total station, and resample the frequency of these records to simulate satellite acquisition parameters (e.g., revisit times and phase ambiguity).…”
Section: Data Methods and Geohazard Domainsmentioning
confidence: 99%
“…Because displacement typically accelerates in each of the 25 aforementioned failure types (Fig. 10C inset), it provides an opportunity for failure forecasting (Voight, 1989;Crosta and Agliardi, 2003;Eberhardt, 2012;Baron and Supper, 2013;Hermanns et al, 2013a;Federico et al, 2015;Moretto et al, 2017).…”
Section: Mechanisms Of Failure 15mentioning
confidence: 99%
“…Possible acceleration in the days or weeks prior to the 2011 landslide cannot be evaluated with the temporal resolution of the displacement histories used here. RADARSAT-2's 24-day revisit period provides low sampling frequency compared to 5 some other RADAR satellites (Moretto et al, 2017) and especially to in-situ sensors or ground-based remote sensors (e.g. Kalaugher et al, 2000;Crosta and Agliardi, 2003;Gischig et al, 2011;Eberhardt, 2012;Federico et al, 2015;Confuorto et al, 2017;Carlà et al, 2018).…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation